Analyzing Women Issues in the second Constituent Assembly Elections (CAE) in Nepal - Guragain, Govinda Prasad (Rural Development Journal, 2017)
This research explores the status of women based primarily on the Constituent Assembly Election (CAE). It provides a framework for future policy and decision-making during national elections to enhance women's empowerment through the electoral system, ensuring their political representation based on democratic principles. The article examines the portrayal of women in Nepali politics by the media from September to December 2013, focusing on the coverage related to the second CA elections. The study employs a qualitative explanatory analysis to argue that the failure of the first CAE to draft a new constitution led to a second CAE within five years. The topic of inclusion, particularly the representation of women, was hotly debated in both elections. While the first CAE was lauded for its inclusiveness, the second one fell short, with fewer women candidates and even fewer winners. The article also delves into the reasons behind the unequal representation of women in the CAE, their issues and demands, and concludes with an overall assessment of the situation.